PENGARUH ETHICAL ORIENTATION DAN REPORTING CHANNEL DALAM MENJELASKAN INTENSI DAN PERILAKU WHISTLE- BLOWING (Studi pada Akuntan Publik di Kota Semarang) - Ailsa Azaria Laksita; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
Findings regarding the low number of employees who report findings of accounting errors or fraud within their companies as well as research gaps from the results of previous studies have encouraged this study to develop and retest a model that is able to explain the low level of whistleblowing behavior. The factors tested for their influence on whistle[1]blowing intention and behavior in this study are ethical orientation and reporting channels.In connection with the aim of the study to develop a research model with ethical orientation and reporting channel variables as predictors of whistle-blowing intention and behavior, data was collected through interviews using questionnaires with accounting staff at the Public Accounting Firm (KAP) in Semarang City who were the research respondents. The collected data is the database to be analyzed using the Structural Equation Modeling (SEM) approach in order to test the model and the influence between variables.The results of statistical tests conducted in this study using empirical data show that the occurrence of whistle-blowing behavior is statistically explained by whistle-blowing intention. The results of this study also show that whistle-blowing intention by respondents is statistically influenced by ethical orientation and reporting channels.